2001
DOI: 10.1021/jo010094a
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereochemically Controlled Formation of Hydroxamic Acid Containinganti- orsyn-1,4-Cycloalkenols from Acylnitroso-Derived Diels−Alder Adducts

Abstract: Treatment of acylnitroso hetero Diels-Alder cycloadducts 2 with iron(III) or copper(II) in an alcohol solvent induces ring opening to afford predominantly monocyclic anti-1,4-hydroxamic acids 3. However, treatment of cycloadducts 2 with copper(II) in toluene reverses the stereoselectivity of the ring opening to afford syn-1,4-hydroxamic acids 4. These regio- and stereoselective processes separately provide anti-1,4- and syn-1,4-disubstituted cyclopentenes while regenerating a hydroxamic acid moiety, thus enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The regio and stereochemically controlled formation of hydroxamic acid containing anti-or syn-1,4-cycloalkenols was reported by M. J. Miller et al [27]. Treatment of acylnitroso hetero-Diels-Alder cycloadducts 48 with iron(III) or copper(II) in an alcohol solvent induces ring opening to afford predominantly monocyclic anti-1,4-hydroxamic acids 49.…”
Section: A Hetero-diels-alder Reactionmentioning
confidence: 81%
“…The regio and stereochemically controlled formation of hydroxamic acid containing anti-or syn-1,4-cycloalkenols was reported by M. J. Miller et al [27]. Treatment of acylnitroso hetero-Diels-Alder cycloadducts 48 with iron(III) or copper(II) in an alcohol solvent induces ring opening to afford predominantly monocyclic anti-1,4-hydroxamic acids 49.…”
Section: A Hetero-diels-alder Reactionmentioning
confidence: 81%
“…The formation of 7 a – b may be rationalized by invoking a cyclopropane ring opening triggered by cleavage of the allylic CO bond (see below) 15gh. Such cleavage is easy under polar conditions18 as shown by the formation of compounds 8 a – b during the cycloaddition between Boc‐nitroso and cycloheptatriene 4 a in CH 3 CN/H 2 O (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The Miller research group reported that Lewis acids could mediate C À O bond cleavage of cycloadducts 91 and 92 in the presence of alcoholic solvents to afford hydroxamates 94-96 (Scheme 17). [109,110] Presumably, this transformation proceeded by coordination of the Lewis acid to the hydroxamate portion of the oxazine system through a structure similar to complex 93. The reaction was found to be moderately selective for 1,4-trans-hydroxamate 94 over 1,2-cis-hydroxamate 96.…”
Section: Cào Bond Cleavagementioning
confidence: 99%